Micropatterning of biomolecules - Yap, Annette Hui Yu. (2010)
Carbon nanotubes (CNT) is the recent star material in the field of electronics such as electrodes, filed-effect transistors (FETs) and sensors due to its unique structure and properties including low resistivity, high current carrying capabilities and high thermal conductivities. In particular, transistors employing CNT as conducting channels are highly sensitive to its local environment, rendering CNT a promising material for chemical and biological sensors.